2001
DOI: 10.1096/fj.00-0296com
|View full text |Cite
|
Sign up to set email alerts
|

Lens epithelial cells derived from αB‐crystallin knockout mice demonstrate hyperproliferation and genomic instability

Abstract: alphaB-crystallin is a member of the small heat shock protein family and can act as a molecular chaperone preventing the in vitro aggregation of other proteins denatured by heat or other stress conditions. Expression of alphaB-crystallin increases in cells exposed to stress and enhanced in tumors of neuroectodermal origin and in many neurodegenerative diseases. In the present study, we examined the properties of lens epithelial cells derived from mice in which the alphaB-crystallin gene had been knocked out. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
67
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 44 publications
6
67
0
1
Order By: Relevance
“…Our previous work with lens epithelial cells cultured from ␣B knockout mice showed that deletion of the ␣B gene permits the emergence of lens epithelial cells with vastly increased proliferative ability (19). In the present work we elucidated mechanistically how ␣B interacts with proteins involved in cell cycle regulation.…”
mentioning
confidence: 63%
See 3 more Smart Citations
“…Our previous work with lens epithelial cells cultured from ␣B knockout mice showed that deletion of the ␣B gene permits the emergence of lens epithelial cells with vastly increased proliferative ability (19). In the present work we elucidated mechanistically how ␣B interacts with proteins involved in cell cycle regulation.…”
mentioning
confidence: 63%
“…Lenses were obtained from 6 -12-week-old mice. To obtain primary lens epithelial cells, capsule/epithelial explants of wild type (129Sv) and ␣BϪ/Ϫ mouse lenses were dissected and cultured in 20% fetal bovine serum-minimal essential medium in 35-mm tissue culture plates as described previously (19,20), and cultured for 1-2 weeks until growth of cells was detectable. Cells were passaged using trypsin-EDTA, and plated in 35-mm plates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary cultures of αB knockout lens epithelial cells demonstrate genomic instability and undergo hyperproliferation at frequency 4 orders of magnitude greater than that predicted by spontaneous immortalization of rodent cells (Andley et al, 2001). Mechanistic studies demonstrate an upregulation of functionally impaired p53 protein .…”
Section: Ensuring the Successful Completion Of Mitosis And Cytokinesismentioning
confidence: 99%